Contracts to devolve health services in fragile states and developing countries: do ethics matter?. Issue 9 (28th August 2009) - Jayasinghe, S
Abstract : Fragile states and developing countries increasingly contract out health services to non-state providers (NSPs) (such as non-governmental organisations, voluntary sector and private sector). The paper identifies ethical issues when contracts involve devolution of health services to NSPs and proposes procedures to prevent or resolve these ethical dilemmas. Ethical issues were identified by examining processes of contracting out. Health needs could be used to select areas to be contracted out and to identify service needs. Health needs comprise "disease-burden-related needs", "health-service needs", and "urgency of health-service needs". The mix of services should include an analysis of cost-effectiveness. NSPs should be selected fairly, without bias, and conflicts of interest during their work must be avoided. The population's views must be respected and accountability structures established. Devolved health services should ensure equity of access to healthcare. The services ought to be sustainable and evaluated objectively. Of these issues, conflicts of interest among NSPs and sustainability of health services have not attracted attention in the literature on ethics of health policy. Fair procedures could address these ethical issues—for example, public consultation on issues; decisions based on the public consultation and made on evidence; principles of decisions stated and reasonable; decisions given adequate publicity; a mechanism established to challenge decisions; assurance that mechanisms meet the above conditions; and regular review of the policies. These procedures are complemented by improving self-governance of NSPs, countries' development of guidelines for devolving health services, and measures to educate the public of the client countries on these issues.